Individualized Target Fortification of Breast Milk: Optimizing Macronutrient Content Using Different Fortifiers and Approaches - Fusch, Stephanie; Fusch, Gerhard; Yousuf, Efrah I.; Rochow, Markus; So, Hon Yiu; Fusch, Christoph; Rochow, Niels (Frontiers in Nutrition, 2021)
Background: Native breast milk composition displays significant inter- and intra-individual variation which persists after standard fortification with fixed doses and challenges target fortification. This study aims to analyze the macronutrient composition of different commercially available fortifiers and the effect of different fortification strategies on nutritional intake of preterm infants. Methods: In 103 preterm infants, native breast milk samples were collected from 24-h feeding batches (n = 3,338) and fat, protein and carbohydrate contents were analyzed. Nutrient content was compared for breast milk that had undergone either (i) standard fortification, (ii) targeted fortification, (iii) selective batching according to breast milk composition, or (iv) partial lyophilization. For (i) eight commercially available standard fortifiers were tested. Targeted fortification (ii) involved the addition of single component modulars of either protein, fat or carbohydrates to standard fortified breast milk. Using a mathematical growth model, the combined effect of protein, fat and carbohydrate intake on growth was assessed. The best composition of standard fortifiers as the initial step for target fortification was explored assuming three clinical scenarios for milk analysis. Results: Macronutrient content was highly variable between native breast milk samples, and this variation was still present after standard fortification, however at elevated macronutrient levels. Standard fortification, breast milk batching, as well as partial lyophilization of human milk resulted in deficient and imbalanced enteral intakes in a significant proportion of infants. Target fortification reduced this variation in a, respectively, higher percentage of samples. The effect size was dependent on the number of measurements per week. The optimum composition of standard fortifiers was dependent on the clinical scenario (measurement frequency) for target fortification. Conclusions: To provide precise and accurate intakes of macronutrients, breast milk should be target fortified. Standard fortified breast milk can result in excess above recommended intakes of some macronutrients which limits the efficiency of target fortification. Standard fortifiers with improved composition are needed for target fortification.